Miedos locales, miedos transnacionales: los católicos y la revolución social a comienzos del siglo XX - Martín O. Castro (Nuevo mundo - Mundos Nuevos, 2020)
The celebrations for the Centenary and, even more so, the Russian Revolution led to the Argentine ruling elites revisiting the social fears and anxiety from the previous decade, but in a more real way. Reactions within the Catholic realm were not homogeneous and resembled the debates among political circles that fluctuated between an intransigent conception that saw socialism and anarchism as foreign, and those who proposed social reform. Many Catholic responses were built upon the belief that liberalism and anticlericalism had opened the doors to the rising of individualism and, eventually, socialism. Even though intellectuals and Catholic leaders shared this diagnosis, they held different positions in the face of their fears of social revolution and about how to avoid it. These views went from an outright institutional or social repression to policies based on social Catholicism. This brief text aims at sketching the Catholic views regarding social revolution and the international scenario in the aftermath of the Great War. To do so, it pays attention to Gustavo Franceschi’s works and to the Catholic newspaper El Pueblo in the final years of the war.